Pneumococcal Diseases in Colombia: Epidemiological Analysis Before and During the Universal Children Immunization against Streptococcus pneumoniae in the Light of a Vaccine Change in 2022 - Carlos Torres-Martínez (Asociación Colombiana de Infectología, 2024)
Streptococcus pneumoniae causes meningitis, pneumonia and bacteremia, mainly in children under 5 years of age and in the elderly. Pneumococcal conjugate vaccines (PCVs) have been administered globally since the year 2000, contributing to substantially reduce the incidence of pneumococcal diseases (PDs). In 2012, Colombia implemented universal vaccination with PCV10 in children under 2 years of age, achieving a decrease and stabilization of the incidence of PDs. However, since 2014, replacement of vaccine serotypes by non-vaccine serotypes, such as 3 and 19A, predominantly, has been observed. Likewise, in 2019, there was an increase in the incidence of meningitis, coinciding with the increase of multi-resistant 19A clones. In July 2022, the vaccine formulation was changed to PCV13, which also has the potential to control serotypes 3, 6A, and 19A. This paper reviews the epidemiology of pneumococcus in Colombia, before and during the uni-versal PCV10 vaccination.